2021
DOI: 10.1073/pnas.2014242118
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for p50RhoGAP BCH domain–mediated regulation of Rho inactivation

Abstract: Spatiotemporal regulation of signaling cascades is crucial for various biological pathways, under the control of a range of scaffolding proteins. The BNIP-2 and Cdc42GAP Homology (BCH) domain is a highly conserved module that targets small GTPases and their regulators. Proteins bearing BCH domains are key for driving cell elongation, retraction, membrane protrusion, and other aspects of active morphogenesis during cell migration, myoblast differentiation, and neuritogenesis. We previously showed that the BCH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Crystallographic analysis reveals that Kal bSec14 exhibits clear structural homology to the αβα fold of canonical CRAL_TRIO domains; a similar fold is observed in the BCH domain of p50RhoGAP even though one of its five strands is contributed by the other monomer present in its intertwined dimer 15 . However, Kal bSec14 adopts a closed conformation in which H7, the presumed gate helix, blocks access to its fragmented hydrophobic interior, leading to the discovery of its alternate ligand binding site.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Crystallographic analysis reveals that Kal bSec14 exhibits clear structural homology to the αβα fold of canonical CRAL_TRIO domains; a similar fold is observed in the BCH domain of p50RhoGAP even though one of its five strands is contributed by the other monomer present in its intertwined dimer 15 . However, Kal bSec14 adopts a closed conformation in which H7, the presumed gate helix, blocks access to its fragmented hydrophobic interior, leading to the discovery of its alternate ligand binding site.…”
Section: Discussionmentioning
confidence: 83%
“…In agreement with this observation, Sec14 domain and SR removal reveals the full transforming activity of MCF2 and MCF2L, identifying an autoinhibitory intramolecular interaction of the Sec14 domain with the GEF PH domain 44 , 45 . A subset of BCH-domain containing RhoGAPs, much like their GEF counterparts, use an autoinhibitory interaction of their BCH and GAP domains to control activity 15 , 46 , 47 . As the postulated non-protein ligands for the SecSR-containing proteins are currently unknown, an exciting possibility is that the SecSR domain may directly interact with the small GTPase or its post-translationally modified protein terminus to regulate signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that BNIP‐2 in epithelial cells activate RhoA by scaffolding RhoGEF GEH‐H1 upon microtubule depolymerization [ 28 ] whereas its homologous BCH domain in p50RhoGAP can control how its adjacent RhoGAP domain functions toward Rho. [ 27 ] It is currently unknown which RhoGEF or RhoGAP may be involved in the process of BNIP‐2‐dependent cardiomyoblast differentiation. Moreover, it remains an interesting prospect to dissect how cells can sense and generate the contractile force through BNIP‐2 and RhoA, and then transduce such mechanical signals into promoting its biochemical scaffolding function that enables LATS to phosphorylate YAP in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] BCH domain‐containing proteins can form homodimers and heterodimers with other BCH domain‐containing proteins and have been demonstrated as a versatile scaffold that regulates small GTPases MAPK and metabolic signaling [ 23 ] and that it engages Rho via a novel Rho‐binding and lipid‐binding motif. [ 27 ] Recently, BNIP‐2 has been reported to be a scaffold protein which engage GEF‐H1 to regulate RhoA activation and cell migration in cancer cells. [ 28 ] In addition, BNIP‐2 is important for skeletal muscle differentiation by CDO‐dependent p38MAPK activation.…”
Section: Introductionmentioning
confidence: 99%